Intimate Partner Violence and Health Conditions Among U.S. Adults—National Intimate Partner Violence Survey, 2010–2012 - Gilbert, Leah K. (Journal of interpersonal violence, 2023)
Introduction: Few studies of intimate partner violence and health outcomes include multiple forms of intimate partner victimization, so this paper sought to examine health associations with intimate partner violence (IPV), including sexual, physical, stalking, and psychological forms, as well as polyvictimization.Methods: Data are from the 2010-2012 National Intimate Partner and Sexual Violence Survey, an on-going national random-digit-dial telephone survey of U.S. adults. There were 41,174 respondents. Logistic regression was used to compute prevalence ratios for any IPV, adjusted for demographics and non-IPV victimization. For individual forms of IPV, prevalence ratios were further adjusted for other forms of IPV. Tests for linear trend in poly-victimization were performed.Results: Any IPV was associated with all health conditions for both sexes with a few exceptions for males. Female penetrative sexual victimization and male stalking victimization were associated with the most health conditions. For each health condition, a significant linear trend indicated that as the number of forms of IPV experienced increased, prevalence of each health condition increased, with a few exceptions for males.Conclusions: It is important for service providers to screen for multiple forms of IPV, including psychological aggression, because individual forms or polyvictimization may have unique and cumulative health effects.